Phylogenomic analyses reveal introgression and cryptic speciation in the globally distributed, vector-transmitted pathogen Plasmodium relictum - Esther Weyer; Angela N. Theodosopoulos; Vaidas Palinauskas; Staffan Bensch; Helena Westerdahl; Mélanie Duc; Arif Ciloglu; Xi Huang; Kyeong Soon Kim; Yoshio Tsuda; Carter T. Atkinson; Pavel Zehtindjiev; et al. (Molecular Phylogenetics and Evolution, 2026)

Comparative Effects of Thermal Recovery Strategies on Strength, Muscle Soreness and Molecular Markers Following Exercise-Induced Muscle Damage in Healthy Adults - F. Bayne; M. Nagyova; N. Stolk; M.A. Placido; M. Hamdi; A. Falzon; R. Perezen; S. Neto Menezes; S. Haliti; C. Atkinson; S. Racinais; N. Gaoua (Journal of Thermal Biology, 2026)

Hatchery-reared coho salmon develop less otolith deformities in tanks with alternating water flow directions - Leigh P. Gaffney; Emma B. Polard; Lydia N. Walton; Chloe Kraemer; Zoe A. Molder; Garth A. Covernton; Jamieson Atkinson; Laura Elmer; Samantha James; Thomas Negrin; Micah Quindazzi; Will Duguid; et al. (Aquaculture, 2026)

Activation of the alternative complement pathway and its relevance for sodium retention in experimental nephrotic syndrome - Daniel Essigke; M. Zaher Kalo; Lingsi Kong; Matthias Wörn; Mohammad-Khaled Saad; Kingsley Omage; Bernhard N. Bohnert; Andreas L. Birkenfeld; John P. Atkinson; Xiaobo Wu; Ferruh Artunc (Pflügers Archiv - European Journal of Physiology, 2026)
The complement component C3, factor B (FB) and factor D (FD) belong to the alternative complement pathway and have been identified in urine samples from nephrotic mice. However, it is not yet known whether these factors are involved in mediating sodium retention in nephrotic syndrome (NS). Here we used a genetic mouse model of NS based on an inducible podocin deletion ( Nphs2 Δipod ). These mice were intercrossed with mice deficient for FB, FD or C3, yielding Nphs2 Δipod *Cfb −/− , Nphs2 Δipod *Cfd −/− or Nphs2 Δipod *C3 −/− mice, respectively. NS was induced after oral doxycycline treatment for 14 days. C3, FB and FD were detected in the nephrotic urine of Nphs2 Δipod mice as well as fragments of C3 and FB, indicating intrarenal activation of the alternative complement pathway. Lack of FB and FD had no impact on the activation of C3. Immunohistochemistry demonstrated positive C3 staining in protein casts and within the proximal tubule. Nephrotic mice of all genotypes experienced similar proteolytic activation of the epithelial sodium channel ENaC, developed sodium retention (urinary sodium concentration < 20 mM) and body weight gain. This was associated with a stimulation of proteolytic processing of epithelial sodium channel ENaC in all genotypes. In conclusion, components of the alternative complement pathway are detectable and activated in nephrotic syndrome. Mice with deletion of C3, FB or FD are not protected from proteolytic ENaC activation and sodium retention in NS.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Controls on regional sulphate distribution in shallow groundwater in the western Canadian Interior Plains - J.E. Liggett; K.E. Pooley; N. Atkinson; P. Humez; S. Thistle; B.D. Smerdon; M. Babakhani; C.N. McClain; B. Mayer (Science of The Total Environment, 2024)

Icing‐related injuries in polar bears ( Ursus maritimus ) at high latitudes - Kristin L. Laidre; Stephen N. Atkinson (Ecology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Labrador Coastal Current and productivity variations offshore Nain (Nunatsiavut) during the late Holocene - M. Atkinson; A. Normandeau; N. Van Nieuwenhove; A. de Vernal; M. Saunders; J. Woollett; A. Limoges (Quaternary Science Reviews, 2024)

Observing change in pelagic animals as sampling methods shift: the case of Antarctic krill - Simeon L. Hill; Angus Atkinson; Javier A. Arata; Anna Belcher; Susan Bengtson Nash; Kim S. Bernard; Alison Cleary; John A. Conroy; Ryan Driscoll; Sophie Fielding; Hauke Flores; Jaume Forcada; et al. (Frontiers in Marine Science, 2024)
Understanding and managing the response of marine ecosystems to human pressures including climate change requires reliable large-scale and multi-decadal information on the state of key populations. These populations include the pelagic animals that support ecosystem services including carbon export and fisheries. The use of research vessels to collect information using scientific nets and acoustics is being replaced with technologies such as autonomous moorings, gliders, and meta-genetics. Paradoxically, these newer methods sample pelagic populations at ever-smaller spatial scales, and ecological change might go undetected in the time needed to build up large-scale, long time series. These global-scale issues are epitomised by Antarctic krill ( Euphausia superba ), which is concentrated in rapidly warming areas, exports substantial quantities of carbon and supports an expanding fishery, but opinion is divided on how resilient their stocks are to climatic change. Based on a workshop of 137 krill experts we identify the challenges of observing climate change impacts with shifting sampling methods and suggest three tractable solutions. These are to: improve overlap and calibration of new with traditional methods; improve communication to harmonise, link and scale up the capacity of new but localised sampling programs; and expand opportunities from other research platforms and data sources, including the fishing industry. Contrasting evidence for both change and stability in krill stocks illustrates how the risks of false negative and false positive diagnoses of change are related to the temporal and spatial scale of sampling. Given the uncertainty about how krill are responding to rapid warming we recommend a shift towards a fishery management approach that prioritises monitoring of stock status and can adapt to variability and change.

Relative sea‐level changes in southeastern Australia during the 19 th and 20 th centuries - S. L. Williams; E. Garrett; P. T. Moss; S. Dangendorf; F. D. Hibbert; N. R. Atkinson; V. Pashley; I. L. Millar; M. H. Garnett; A. Zawadzki; W. R. Gehrels (Journal of Quaternary Science, 2023)
Rates of global and regional sea‐level rise between ~1850 and 1950 were high compared to those in preceding centuries. The cause of this sea‐level acceleration remains uncertain, but it appears to be pronounced in a small set of relative sea‐level proxy records from the Southern Hemisphere. Here we generate three new proxy‐based relative sea‐level reconstructions for southeastern Australia to investigate spatial patterns and causes of historical sea‐level changes in the Tasman Sea. Palaeo sea‐level estimates were determined using salt‐marsh foraminifera as sea‐level indicators. Records are underpinned by chronologies based on accelerator mass spectrometry 14 C, radiogenic lead ( 210 Pb), stable lead isotopes and palynological analyses. Our reconstructions show that relative sea level rose by ~0.2–0.3 m over the last 200 years in southeastern Australia, and rates of sea‐level rise were especially high over the first half of the 20 th century. Based on modelled estimates of the contributing components to sea‐level rise, we suggest that the episode of rapid sea‐level rise was driven by barystatic contributions, but sterodynamic contributions were dominant by the mid‐20 th century. Significant spatial variability in relative sea level indicates that local to sub‐regional drivers of sea level are also prominent. Our reconstructions significantly enhance our understanding of the spatiotemporal pattern of early 20 th century sea‐level rise in the region.

Lethal and Sub-lethal Implications of Sodium Chloride Exposure for Adult Unionid Mussel Species: Eurynia dilatata and Lasmigona costata - Erika A. Burton; Brian Atkinson; Joseph Salerno; Hufsa N. Khan; Ryan S. Prosser; Patricia L. Gillis (Archives of Environmental Contamination and Toxicology, 2023)
The elevated use of salt as a de-icing agent on roads in Canada is causing an increase in the chloride concentration of freshwater ecosystems. Freshwater Unionid mussels are a group of organisms that are sensitive to increases in chloride levels. Unionids have greater diversity in North America than anywhere else on Earth, but they are also one of the most imperiled groups of organisms. This underscores the importance of understanding the effect that increasing salt exposure has on these threatened species. There are more data on the acute toxicity of chloride to Unionids than on chronic toxicity. This study investigated the effect of chronic sodium chloride exposure on the survival and filtering activity of two Unionid species ( Eurynia dilatata, and Lasmigona costata ) and assessed the effect on the metabolome in L. costata hemolymph. The concentration causing mortality after 28 days of exposure was similar for E. dilatata (1893 mg Cl − /L) and L. costata (1903 mg Cl − /L). Significant changes in the metabolome of the L. costata hemolymph were observed for mussels exposed to non-lethal concentrations. For example, several phosphatidylethanolamines, several hydroxyeicosatetraenoic acids, pyropheophorbide-a, and alpha-linolenic acid were significantly upregulated in the hemolymph of mussels exposed to 1000 mg Cl − /L for 28 days. While no mortality occurred in the treatment, elevated metabolites in the hemolymph are an indicator of stress.

An on-ice aerial survey of the Kane Basin polar bear (Ursus maritimus) subpopulation - Øystein Wiig; Stephen N. Atkinson; Erik W. Born; Seth Stapleton; Todd Arnold; Markus Dyck; Kristin L. Laidre; Nicholas J. Lunn; Eric V. Regehr (Polar Biology, 2022)
There is an imminent need to collect information on distribution and abundance of polar bears ( Ursus maritimus ) to understand how they are affected by the ongoing decrease in Arctic sea ice. The Kane Basin (KB) subpopulation is a group of high-latitude polar bears that ranges between High Arctic Canada and NW Greenland around and north of the North Water polynya (NOW). We conducted a line transect distance sampling aerial survey of KB polar bears during 28 April–12 May 2014. A total of 4160 linear kilometers were flown in a helicopter over fast ice in the fjords and over offshore pack ice between 76° 50′ and 80° N′. Using a mark-recapture distance sampling protocol, the estimated abundance was 190 bears (95% lognormal CI: 87–411; CV 39%). This estimate is likely negatively biased to an unknown degree because the offshore sectors of the NOW with much open water were not surveyed because of logistical and safety reasons. Our study demonstrated that aerial surveys may be a feasible method for obtaining abundance estimates for small subpopulations of polar bears.

Advancing Social Equity in and Through Marine Conservation - Nathan J. Bennett; Laure Katz; Whitney Yadao-Evans; Gabby N. Ahmadia; Scott Atkinson; Natalie C. Ban; Neil M. Dawson; Asha de Vos; Juno Fitzpatrick; David Gill; Mael Imirizaldu; Naia Lewis; et al. (Frontiers in Marine Science, 2021)
Substantial efforts and investments are being made to increase the scale and improve the effectiveness of marine conservation globally. Though it is mandated by international law and central to conservation policy, less attention has been given to how to operationalize social equity in and through the pursuit of marine conservation. In this article, we aim to bring greater attention to this topic through reviewing how social equity can be better integrated in marine conservation policy and practice. Advancing social equity in marine conservation requires directing attention to: recognition through acknowledgment and respect for diverse peoples and perspectives; fair distribution of impacts through maximizing benefits and minimizing burdens; procedures through fostering participation in decision-making and good governance; management through championing and supporting local involvement and leadership; the environment through ensuring the efficacy of conservation actions and adequacy of management to ensure benefits to nature and people; and the structural barriers to and institutional roots of inequity in conservation. We then discuss the role of various conservation organizations in advancing social equity in marine conservation and identify the capacities these organizations need to build. We urge the marine conservation community, including governments, non-governmental organizations and donors, to commit to the pursuit of socially equitable conservation.

Filter-feeders have differential bottom-up impacts on green and brown food webs - Carla L. Atkinson; Halvor M. Halvorson; Kevin A. Kuehn; Monica Winebarger; Ansley Hamid; Matthew N. Waters (Oecologia, 2021)

Trawl fishing impacts on the status of seabed fauna in diverse regions of the globe - Tessa Mazor; C. Roland Pitcher; Wayne Rochester; Michel J. Kaiser; Jan G. Hiddink; Simon Jennings; Ricardo Amoroso; Robert A. McConnaughey; Adriaan D. Rijnsdorp; Ana M. Parma; Petri Suuronen; Jeremy Collie; et al. (Fish and Fisheries, 2021)
Bottom trawl fishing is a controversial activity. It yields about a quarter of the world's wild seafood, but also has impacts on the marine environment. Recent advances have quantified and improved understanding of large‐scale impacts of trawling on the seabed. However, such information needs to be coupled with distributions of benthic invertebrates (benthos) to assess whether these populations are being sustained under current trawling regimes. This study collated data from 13 diverse regions of the globe spanning four continents. Within each region, we combined trawl intensity distributions and predicted abundance distributions of benthos groups with impact and recovery parameters for taxonomic classes in a risk assessment model to estimate benthos status. The exposure of 220 predicted benthos‐group distributions to trawling intensity (as swept area ratio) ranged between 0% and 210% (mean = 37%) of abundance. However, benthos status, an indicator of the depleted abundance under chronic trawling pressure as a proportion of untrawled state, ranged between 0.86 and 1 (mean = 0.99), with 78% of benthos groups > 0.95. Mean benthos status was lowest in regions of Europe and Africa, and for taxonomic classes Bivalvia and Gastropoda. Our results demonstrate that while spatial overlap studies can help infer general patterns of potential risk, actual risks cannot be evaluated without using an assessment model that incorporates trawl impact and recovery metrics. These quantitative outputs are essential for sustainability assessments, and together with reference points and thresholds, can help managers ensure use of the marine environment is sustainable under the ecosystem approach to management.

Transient benefits of climate change for a high‐Arctic polar bear ( Ursus maritimus ) subpopulation - Kristin L. Laidre; Stephen N. Atkinson; Eric V. Regehr; Harry L. Stern; Erik W. Born; Øystein Wiig; Nicholas J. Lunn; Markus Dyck; Patrick Heagerty; Benjamin R. Cohen (Global Change Biology, 2020)
Kane Basin (KB) is one of the world's most northerly polar bear ( Ursus maritimus ) subpopulations, where bears have historically inhabited a mix of thick multiyear and annual sea ice year‐round. Currently, KB is transitioning to a seasonally ice‐free region because of climate change. This ecological shift has been hypothesized to benefit polar bears in the near‐term due to thinner ice with increased biological production, although this has not been demonstrated empirically. We assess sea‐ice changes in KB together with changes in polar bear movements, seasonal ranges, body condition, and reproductive metrics obtained from capture–recapture (physical and genetic) and satellite telemetry studies during two study periods (1993–1997 and 2012–2016). The annual cycle of sea‐ice habitat in KB shifted from a year‐round ice platform (~50% coverage in summer) in the 1990s to nearly complete melt‐out in summer ( p = .004). Between the 1990s and 2010s, adult female (AF) seasonal ranges more than doubled in spring and summer and were significantly larger in all months. Body condition scores improved for all ages and both sexes. Mean litter sizes of cubs‐of‐the‐year (C0s) and yearlings (C1s), and the number of C1s per AF, did not change between decades. The date of spring sea‐ice retreat in the previous year was positively correlated with C1 litter size, suggesting smaller litters following years with earlier sea‐ice breakup. Our study provides evidence for range expansion, improved body condition, and stable reproductive performance in the KB polar bear subpopulation. These changes, together with a likely increasing subpopulation abundance, may reflect the shift from thick, multiyear ice to thinner, seasonal ice with higher biological productivity. The duration of these benefits is unknown because, under unmitigated climate change, continued sea‐ice loss is expected to eventually have negative demographic and ecological effects on all polar bears.

Effects of the cannabinoid receptor agonist CP-55,940 on incentive salience attribution - Ali Gheidi; Lora M. Cope; Christopher J. Fitzpatrick; Benjamin N. Froehlich; Rachel Atkinson; Coltrane K. Groves; Clair N. Barcelo; Jonathan D. Morrow (Psychopharmacology, 2020)

Evidence for a novel subcortical mechanism for posterior cingulate cortex atrophy in HIV peripheral neuropathy - John R. Keltner; Alan Tong; Eelke Visser; Mark Jenkinson; Colm G. Connolly; Alyssa Dasca; Aleks Sheringov; Zachary Calvo; Earl Umbao; Rohit Mande; Mary Beth Bilder; Gagandeep Sahota; et al. (Journal of NeuroVirology, 2020)

India’s contribution to mitigating the impacts of climate change through vegetation management - J. Dash; M. D. Behera; C. Jeganathan; C. S. Jha; S. Sharma; R. Lucas; A. A. Khuroo; A. Harris; P. M. Atkinson; D. S. Boyd; C. P. Singh; M. P. Kale; et al. (Tropical Ecology, 2020)

Mouse models of high-risk neuroblastoma - Alvin Kamili; Caroline Atkinson; Toby N. Trahair; Jamie I. Fletcher (Cancer and Metastasis Reviews, 2020)

Dose evaluation of intravenous metamizole (dipyrone) in infants and children: a prospective population pharmacokinetic study - Victoria C. Ziesenitz; Frédérique Rodieux; Andrew Atkinson; Carole Borter; Julia A. Bielicki; Manuel Haschke; Urs Duthaler; Fabio Bachmann; Thomas O. Erb; Nicolas Gürtler; Stefan Holland-Cunz; Johannes N. van den Anker; et al. (European Journal of Clinical Pharmacology, 2019)

Determinants of food resource assimilation by stream insects along a tropical elevation gradient - Carla L. Atkinson; Andrea C. Encalada; Amanda T. Rugenski; Steve A. Thomas; Andrea Landeira-Dabarca; N. LeRoy Poff; Alexander S. Flecker (Oecologia, 2018)

Localised cutaneous microvascular adaptation to exercise training in humans - Ceri L. Atkinson; Howard H. Carter; Dick H. J. Thijssen; Gurpreet K. Birk; N. Timothy Cable; David A. Low; Floortje Kerstens; Iris Meeuwis; Ellen A. Dawson; Daniel J. Green (European Journal of Applied Physiology, 2018)

Patterns and trends of pediatric bloodstream infections: a 7-year surveillance study - N. Buetti; A. Atkinson; L. Kottanattu; J. Bielicki; J. Marschall; A. Kronenberg (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Reference Intervals of Mineral Elements in Plasma of Anesthetized Free-Ranging Adult Females of South American Sea Lion, Otaria flavescens - Paula S. Polizzi; L. N. Chiodi Boudet; A. Ponce de León; M. Quiroga; D. H. Rodríguez; S. Atkinson; M. S. Gerpe (Biological Trace Element Research, 2016)

Influence of nocturnal and daytime sleep on initial orthostatic hypotension - N. C. S. Lewis; H. Jones; P. N. Ainslie; A. Thompson; K. Marrin; G. Atkinson (European Journal of Applied Physiology, 2015)

A glacial cryptic refuge in south‐east Australia: human occupation and mobility from 36 000 years ago in the Sydney Basin, New South Wales - ALAN N. WILLIAMS; FENELLA ATKINSON; MICHELLE LAU; PHILLIP S. TOMS (Journal of Quaternary Science, 2014)
Excavations across a source‐bordering dune overlooking the Hawkesbury River in north‐west Sydney, Australia, suggest initial occupation of the region by at least 36 ka, with variable but uninterrupted use until the early Holocene; following abandonment, the site was then re‐occupied by ∼3 ka. Along with a handful of other sites, the results provide the earliest reliable evidence of permanent regional populations within south‐eastern Australia, and support a model in which early colonizers followed the coastal fringe with forays along the main river systems. The evidence is consistent with the demographic model of Williams, 2013 ( Proceedings of the Royal Society Series B 280 : 20130486), which suggested low, but established regional populations before the Last Glacial Maximum (LGM), a population nadir following the LGM and increasing use of the region from ∼12 to 8 ka. The site exhibits increased use at the onset and peak of the LGM, and provides an example of a cryptic refuge as defined by Smith, 2013 ( The Archaeology of Australia's Deserts . Cambridge University Press: New York). Specifically, changing artefact densities and attributes show the site was used repeatedly, but for shorter periods through this time, and suggest it formed one of a series of key localities in a point‐to‐point (rather than home‐base) subsistence strategy. This strategy was maintained until the site's abandonment in the early Holocene, despite changing population and climatic conditions through the Terminal Pleistocene.

Accounting for the Impact of Conservation on Human Well‐Being - E.J. MILNER‐GULLAND; J.A. MCGREGOR; M. AGARWALA; G. ATKINSON; P. BEVAN; T. CLEMENTS; T. DAW; K. HOMEWOOD; N. KUMPEL; J. LEWIS; S. MOURATO; B. PALMER FRY; et al. (Conservation Biology, 2014)
Conservationists are increasingly engaging with the concept of human well‐being to improve the design and evaluation of their interventions. Since the convening of the influential Sarkozy Commission in 2009, development researchers have been refining conceptualizations and frameworks to understand and measure human well‐being and are starting to converge on a common understanding of how best to do this. In conservation, the term human well‐being is in widespread use, but there is a need for guidance on operationalizing it to measure the impacts of conservation interventions on people. We present a framework for understanding human well‐being, which could be particularly useful in conservation. The framework includes 3 conditions; meeting needs, pursuing goals, and experiencing a satisfactory quality of life. We outline some of the complexities involved in evaluating the well‐being effects of conservation interventions, with the understanding that well‐being varies between people and over time and with the priorities of the evaluator. Key challenges for research into the well‐being impacts of conservation interventions include the need to build up a collection of case studies so as to draw out generalizable lessons; harness the potential of modern technology to support well‐being research; and contextualize evaluations of conservation impacts on well‐being spatially and temporally within the wider landscape of social change. Pathways through the smog of confusion around the term well‐being exist, and existing frameworks such as the Well‐being in Developing Countries approach can help conservationists negotiate the challenges of operationalizing the concept. Conservationists have the opportunity to benefit from the recent flurry of research in the development field so as to carry out more nuanced and locally relevant evaluations of the effects of their interventions on human well‐being. Consideración del Impacto de la Conservación sobre el Bienestar Humano

Diurnal variation in the salivary melatonin responses to exercise: relation to exercise-mediated tachycardia - K. Marrin; B. Drust; W. Gregson; C. J. Morris; N. Chester; G. Atkinson (European Journal of Applied Physiology, 2011)

Integrated catchment management—interweaving social process and science knowledge - A Fenemor; C Phillips; W Allen; RG Young; G Harmsworth; B Bowden; L Basher; PA Gillespie; M Kilvington; R Davies‐Colley; J Dymond; A Cole; et al. (New Zealand Journal of Marine and Freshwater Research, 2011)
This paper provides an overview of the Motueka integrated catchment management (ICM) research programme. This research was based on the thesis that achieving ecosystem resilience at a catchment scale requires active measures to develop community resilience. We define a generic adaptive planning and action process, with associated knowledge management and stakeholder involvement processes, and illustrate those processes with observations from five research themes: (1) water allocation; (2) land use effects on water; (3) land and freshwater impacts on the coast; (4) integrative tools and processes for managing cumulative effects; and (5) building human capital and facilitating community action. Our research clearly illustrates the benefits for effective decision‐making of carrying out catchment scale science and management within collaborative processes which patiently develop trusting relationships. We conclude that coastal catchments should be managed as a holistic continuum from ridge tops to the sea and that some processes like floods or loss of community resilience have decadal consequences, which support the need for long‐term monitoring and investment.

Cadmium, Copper, Iron, and Zinc Concentrations in Kidneys of Grey Wolves, Canis lupus, from Alaska, Idaho, Montana (USA) and the Northwest Territories (Canada) - S. R. Hoffmann; S. A. Blunck; K. N. Petersen; E. M. Jones; J. C. Koval; R. Misek; J. A. Frick; H. D. Cluff; C. A. Sime; M. McNay; K. B. Beckman; M. W. Atkinson; et al. (Bulletin of Environmental Contamination and Toxicology, 2010)

Circadian variation in the circulatory responses to exercise: relevance to the morning peaks in strokes and cardiac events - Greg Atkinson; Helen Jones; Philip N. Ainslie (European Journal of Applied Physiology, 2010)

Evidence for widespread cryptic sexual generations in apparently purely asexual Andricus gallwasps - GRAHAM N. STONE; RACHEL J. ATKINSON; ANTONIS ROKAS; JOSÉ‐LUIS NIEVES ALDREY; GEORGE MELIKA; ZOLTAN Ács; GYÖRGY CSÓKA; ALEXANDER HAYWARD; RICHARD BAILEY; CAROLINE BUCKEE; GILEAN A. T. McVEAN (Molecular Ecology, 2008)
Oak gallwasps (Hymenoptera, Cynipidae, Cynipini) are one of seven major animal taxa that commonly reproduce by cyclical parthenogenesis (CP). A major question in research on CP taxa is the frequency with which lineages lose their sexual generations, and diversify as purely asexual radiations. Most oak gallwasp species are only known from an asexual generation, and secondary loss of sex has been conclusively demonstrated in several species, particularly members of the holarctic genus Andricus. This raises the possibility of widespread secondary loss of sex in the Cynipini, and of diversification within purely parthenogenetic lineages. We use two approaches based on analyses of allele frequency data to test for cryptic sexual generations in eight apparently asexual European species distributed through a major western palaearctic lineage of the gallwasp genus Andricus . All species showing adequate levels of polymorphism (7/8) showed signatures of sex compatible with cyclical parthenogenesis. We also use DNA sequence data to test the hypothesis that ignorance of these sexual generations (despite extensive study on this group) results from failure to discriminate among known but morphologically indistinguishable sexual generations. This hypothesis is supported: 35 sequences attributed by leading cynipid taxonomists to a single sexual adult morphospecies, Andricus burgundus, were found to represent the sexual generations of at least six Andricus species. We confirm cryptic sexual generations in a total of 11 Andricus species, suggesting that secondary loss of sex is rare in Andricus .

Unusual new Chaetosphaeria species from New Zealand: Intrafamilial diversity and elucidations of the Chaetosphaeriaceae ‐Lasiosphaeriaceae relationship (Sordariomycetes, Ascomycotina) - Toni J. Atkinson; Andrew N. Miller; Sabine M. Huhndorf; David A. Orlovich (New Zealand Journal of Botany, 2007)
Chaetosphaeria albida, C. bombycina , and C. metallicans are described and compared with other Chaetosphaeria taxa using morphological and molecular methods. The fresh ascomata of C. albida are almost white, translucent, and aereolate; they are papillate with a distinctive 4‐layered peridium, and the ascospores are scolecosporous, multiseptate, and hyaline. C. bombycina is similar, but the fresh ascomata are light fawn‐grey with a reflective silken appearance, non‐papillate, and the similar peridium is 3‐layered. C. metallicans has ascomata which are blue‐black, shiny and metallic when fresh; the thick peridium is heavily melanised, and the ascospores are straight to allantoid, 3‐septate, and hyaline. The scolecosporous ascospores of C. albida and C. bombycina would have traditionally referred these taxa to Lasiosphaeria . However, like C. metallicans , they lack a peridial tomentum, and have asci with light‐refractive, non‐amyloid apical rings, without a sub‐apical globule. Despite the major differences in spore shape and ascomal wall structure, analyses of the LSU and ITS regions of ribosomal DNA suggest that genetically all three fall within Chaetosphaeria , near to C. raciborskii , and in a sister clade to the type species C. innumera . The placement of these species considerably expands current morphological conceptions of Chaetosphaeria , particularly in terms of ascomal wall appearance and structure, and confirms the existence of a scolecosporous group within the genus. in the search for morphological characters which mimic genetic relationships, this study further elucidates the relationship between the Chaetosphaeriaceae and the Lasiosphaeriaceae.

The phylogeographical clade trade: tracing the impact of human‐mediated dispersal on the colonization of northern Europe by the oak gallwasp Andricus kollari - GRAHAM N. STONE; RICHARD J. CHALLIS; RACHEL J. ATKINSON; GYÖRGY CSÓKA; ALEX HAYWARD; GEORGE MELIKA; SERAP MUTUN; SONJA PREUSS; ANTONIS ROKAS; EBRAHIM SADEGHI; KARSTEN SCHÖNROGGE (Molecular Ecology, 2007)
Human dispersal of organisms is an important process modifying natural patterns of biodiversity. Such dispersal generates new patterns of genetic diversity that overlie natural phylogeographical signatures, allowing discrimination between alternative dispersal mechanisms. Here we use allele frequency and DNA sequence data to distinguish between alternative scenarios (unassisted range expansion and long range introduction) for the colonization of northern Europe by an oak‐feeding gallwasp, Andricus kollari . Native to Mediterranean latitudes from Portugal to Iran, this species became established in northern Europe following human introduction of a host plant, the Turkey oak Quercus cerris . Colonization of northern Europe is possible through three alternative routes: (i) unassisted range expansion from natural populations in the Iberian Peninsula; (ii) unassisted range expansion from natural populations in Italy and Hungary; or (iii) descent from populations imported to the UK as trade goods from the eastern Mediterranean in the 1830s. We show that while populations in France were colonized from sources in Italy and Hungary, populations in the UK and neighbouring parts of coastal northern Europe encompass allozyme and sequence variation absent from the known native range. Further, these populations show demographic signatures expected for large stable populations, rather than signatures of rapid population growth from small numbers of founders. The extent and spatial distribution of genetic diversity in the UK suggests that these A. kollari populations are derived from introductions of large numbers of individuals from each of two genetically divergent centres of diversity in the eastern Mediterranean. The strong spatial patterning in genetic diversity observed between different regions of northern Europe, and between sites in the UK, is compatible with leptokurtic models of population establishment.

LeMAN4 endo-β-mannanase from ripe tomato fruit can act as a mannan transglycosylase or hydrolase - Roswitha Schröder; Teresa F. Wegrzyn; Neelam N. Sharma; Ross G. Atkinson (Planta, 2006)

Glioma: What is the role of c-Myc, hsp90 and telomerase? - A. Shervington; N. Cruickshanks; H. Wright; R. Atkinson-Dell; R. Lea; G. Roberts; L. Shervington (Molecular and Cellular Biochemistry, 2006)

Modelling spatial distributions of Ceratium hirundnella and Microcystis. in a small productive British lake - R. Hedger; N. Olsen; D. George; T. Malthus; P. Atkinson (Hydrobiologia, 2004)

Out of Anatolia: longitudinal gradients in genetic diversity support an eastern origin for a circum‐Mediterranean oak gallwasp Andricus quercustozae - Antonis Rokas; Rachel J. Atkinson; Lucy Webster; György Csóka; Graham N. Stone (Molecular Ecology, 2003)
Many studies have addressed the latitudinal gradients in intraspecific genetic diversity of European taxa generated during postglacial range expansion from southern refugia. Although Asia Minor is known to be a centre of diversity for many taxa, relatively few studies have considered its potential role as a Pleistocene refugium or a potential source for more ancient westward range expansion into Europe. Here we address these issues for an oak gallwasp, Andricus quercustozae (Hymenoptera: Cynipidae), whose distribution extends from Morocco along the northern coast of the Mediterranean through Turkey to Iran. We use sequence data for a fragment of the mitochondrial gene cytochrome b and allele frequency data for 12 polymorphic allozyme loci to answer the following questions: (1) which regions represent current centres of genetic diversity for A. quercustozae ? Do eastern populations represent one refuge or several discrete glacial refugia? (2) Can we infer the timescale and sequence of the colonization processes linking current centres of diversity? Our results suggest that A. quercustozae was present in five distinct refugia (Iberia, Italy, the Balkans, southwestern Turkey and northeastern Turkey) with recent genetic exchange between Italy and Hungary. Genetic diversity is greatest in the Turkish refugia, suggesting that European populations are either (a) derived from Asia Minor, or (b) subject to more frequent population bottlenecks. Although Iberian populations show the lowest diversity for putatively selectively neutral markers, they have colonized a new oak host and represent a genetically and biologically discrete entity within the species.

Patterns of Hermes transposition in Drosophila melanogaster - N. Guimond; D. K. Bideshi; A. C. Pinkerton; P. W. Atkinson; D. A. O'Brochta (Molecular Genetics and Genomics, 2003)

Trimethyltin-induced neurogenesis in the murine hippocampus - G. Jean Harry; Christopher A. McPherson; Robert N. Wine; Kelly Atkinson; Christian Lefebvre d'Hellencourt (Neurotoxicity Research, 2003)

The incidence and diversity of Wolbachia in gallwasps (Hymenoptera; Cynipidae) on oak - A. Rokas; R. J. Atkinson; J.‐L. Nieves‐Aldrey; S. A. West; G. N. Stone (Molecular Ecology, 2002)
Wolbachia bacteria infect ≈ 20% of all insect species, and cause a range of alterations to host reproduction, including imposition of thelytoky. The incidence and phenotypic impact of Wolbachia remains to be established in many insect taxa, and considerable research effort is currently focused on its association with particular reproductive modes and the relative importance of the various pathways via which infection occurs. Gallwasps represent an attractive system for addressing these issues for two reasons. First, they show a diversity of reproductive modes (including arrhenotoky, thelytoky and cyclical parthenogenesis) in which the impact of Wolbachia infection can be examined. Second, they occupy two intimately linked trophic niches (gall‐inducers and inquilines) between which there is potential for the horizontal exchange of Wolbachia infection. In the arrhenotokous gallwasp lineages screened to date (the herb‐galling ‘Aylacini’ and the rose‐galling Diplolepidini), Wolbachia infection always induces thelytoky. The impact of Wolbachia in other arrhenotokous clades, and in the cyclically parthenogenetic clades remains unknown. Here we use polymerase chain reaction (PCR) screening and sequence data for two Wolbachia genes ( wsp and ftsZ ) to examine the prevalence and incidence of Wolbachia infection in 64 species (a total of 609 individuals) in two further tribes: the arrhenotokous inquilines (tribe Synergini), and the cyclically parthenogenetic oak gallwasps (tribe Cynipini). We ask: (i) whether Wolbachia infection has any apparent impact on host reproduction in the two tribes and (ii) whether there is any correlation between Wolbachia infection and the apparent lack of an arrhenotokous generation in many oak gallwasp life cycles. We show: (i) that Wolbachia infection is rare in the Cynipini. Infected species show no deviation from cyclical parthenogenesis, and infection is no more common in species known only from a thelytokous generation; (ii) that there is a higher incidence of infection within the arrhenotokous inquilines, and generally in gallwasp tribes without cyclical parthenogensis; (iii) all Wolbachia ‐positive inquiline species are known to possess males, implying either that Wolbachia infection does not result in loss of sex in this tribe or, more probably, that (as for some rose gallwasps) Wolbachia infection leads to loss of sex in specific populations; and (iv) although we find some inquilines and gall inducers to be infected with Wolbachia having the same wsp sequence, these hosts are not members of the same gall communities, arguing against frequent horizontal transmission between these two trophic groups. We suggest that exchange may be mediated by the generalist parasitoids common in oak galls.

Transformations of Pesticides in the Atmosphere: A State of the Art - Roger Atkinson; Rob Guicherit; Ronald A. Hites; Wolf-Ulrich Palm; James N. Seiber; Pim de Voogt (Water, Air, & Soil Pollution, 1999)

Atmospheric gas phase loss processes for chlorobenzene, benzotrifluoride, and 4-chlorobenzotrifluoride, and generalization of predictive techniques for atmospheric lifetimes of aromatic compounds - Roger Atkinson; Sara M. Aschmann; Arthur M. Winer; James N. Pitts (Archives of Environmental Contamination and Toxicology, 1985)

A study of the atmospheric reactions of 1,3-dichloropropene and other selected organochlorine compounds - Ernesto C. Tuazon; Roger Atkinson; Arthur M. Winer; James N. Pitts (Archives of Environmental Contamination and Toxicology, 1984)